2018
DOI: 10.17501/iccc.2018.2102
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Monitoring of Wetlands via Remote Sensing and Gis: A Case Study From Turkey

Abstract: Remote sensing that is a low cost data source capable of making temporal observations has more advantages than the traditional methods to obtain land-use/cover change maps. In this study, temporal land-use/cover change of surface water bodies in Konya Closed Basin was evaluated via Landsat satellite images for the past 30 years. The basin, located in Central Anatolia Region of Turkey, faces water scarcity problems; however, wet agricultural activities are still favoured and practiced. Therefore, water resource… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…A noticeable areal change has occurred at Akgol Wetland, that is an internationally recognized water body of the basin, has almost lost its water surface by 96% during a period of 30 years , and thus, it is in danger of extinction (Musaoglu et al, 2018). This finding was the outcome derived from the various satellite images used belonging to different years.…”
Section: Figure2 Flow Chart Of the Methodology Usedmentioning
confidence: 86%
See 1 more Smart Citation
“…A noticeable areal change has occurred at Akgol Wetland, that is an internationally recognized water body of the basin, has almost lost its water surface by 96% during a period of 30 years , and thus, it is in danger of extinction (Musaoglu et al, 2018). This finding was the outcome derived from the various satellite images used belonging to different years.…”
Section: Figure2 Flow Chart Of the Methodology Usedmentioning
confidence: 86%
“…The area of each of these water bodies as well as their conservation status are given in Table 1. Musaoglu et al (2018) conducted a long-term monitoring study of the wetlands in this basin via RS and Geographic Information System (GIS). The results derived indicated that the overall surface area of the water bodies in KCB decreased by approximately 23.5% within the inspection period of 1987-2017.…”
Section: Study Areamentioning
confidence: 99%
“…Groundwater is one of the most valuable and vulnerable freshwater resources [1], which plays a critical role in irrigated agriculture and global food security [2]. In addition, groundwater serves as the primary source of drinking water in both rural and urban areas, providing fresh water storage for domestic, agricultural, and industrial demands, while meeting basic human needs and maintaining the ecological balance and aquatic ecosystems [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…There have been many case studies conducted in this area. In a case study, water bodies of KCB were monitored from 1987 to 2017 by Landsat satellite data associated with meteorological data, a decrement in Akgol wetland area is observed as 96% (Musaoglu et al, 2018). In another case study, adverse impacts of dam constructions on the study area were monitored by Landsat satellite images and meteorological data (Dervisoglu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%